Intellektuaalista terrorismia : Kansainväliset situationistit 1957-72 - Sederholm, Helena (1994)
The Situationist International (SI, 1957-72) was a Marxist political movement which held the view that art and artists constitute a revolutionary potential in society. The SI criticized the cultural practices of the sixties. Denying its own status as a movement, the SI rejected canonization , which was prevalent in the art-world and had burdened earlier avant-garde movements. The situationists wanted to suppress both art and (party) politics which in their view represented capitalist experience and alienation transformed into a spectacle. They set out to replace precious and consumable art objects with techniques enabling a simultaneous experience of the subjects and objects of art, without any specific mediating factors. SI is not so well known movement, especially in Finland. As I know this book is the first Finnish research about Situationists. The analysis focuses on the Situationists' thought on art politics and the movement's relationship to the avant-garde of this century. Considering the SI in a historical perspective, it can be said to have served as an intermediary link between the Dada and Surrealist movements of the first half of this century and Punk and other more marginal movements which emerged during the latter half of the century. The historical avant-garde and the SI had a great deal in common, however. The SI took up the avant-garde project to bring art and life in one, to make them intermingle with each other. Indeed, the SI can be considered the last avant-garde movement, because it took the project of uniting art and life theoretically farthest. The situationists did not settle for a tangential relationship between art and life, materializing only on rare occasions and in special situations, such as happenings or conceptual art. Instead, their aim was to change both life and art to the full. The SI ways of manifesting its views also connects the movement to the tradition of the radical avant-garde. Many of its ideas about art and politics came from Dada, COBRA, Lettrism and other movements. The Situationists' literary style echoed the Surrealists. The SI deserves to be viewed side by side with poststructuralist and even postmodernist thinking. Although the Situationists never took the leap from spectacle to simulacra which Jean Baudrillard later did, they developed such ideas as changing categories of time into categories of space, which some theorists claim typical of the postmodern culture. Furthermore, the SI anticipated such phenomena as the growth of plagiarism and anonymity in cultural production in the eighties.